2020
DOI: 10.1002/cam4.3583
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of combined guadecitabine and cisplatin in platinum refractory germ cell cancer

Abstract: Purpose Germ cell tumors (GCTs) are cured with therapy based on cisplatin, although a clinically significant number of patients are refractory and die of progressive disease. Based on preclinical studies indicating that refractory testicular GCTs are hypersensitive to hypomethylating agents (HMAs), we conducted a phase I trial combining the next‐generation HMA guadecitabine (SGI‐110) with cisplatin in recurrent, cisplatin‐resistant GCT patients. Methods Patients with metastatic GCTs were treated for five conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…This data provided the rationale to combine cisplatin and guadecitabine in a phase Ib study of heavily pretreated cisplatin-resistant TGCT patients [NCT02429466]. This combination was tolerable and showed two major responses and an overall clinical benefit rate of 46% from 14 patients [ 127 ].…”
Section: Epigenetic States In Testicular Germ Cell Tumors Associatmentioning
confidence: 99%
“…This data provided the rationale to combine cisplatin and guadecitabine in a phase Ib study of heavily pretreated cisplatin-resistant TGCT patients [NCT02429466]. This combination was tolerable and showed two major responses and an overall clinical benefit rate of 46% from 14 patients [ 127 ].…”
Section: Epigenetic States In Testicular Germ Cell Tumors Associatmentioning
confidence: 99%
“…Both proof-of-concept studies constitute an argument in favor of using hypomethylating targeted treatments for these resistant patients, which was one of the main research questions investigated in our discovery work. In fact, the same group and others have already shown the benefit of agents such as 5-AZA, DAC and guadecitabine in treating resistant patients and in rescuing sensitivity to cisplatin, both in vitro and including in a recent clinical trial [ 34 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pre-clinical studies, TGCTs were extremely sensitive to low-dose decitabine, a DNA methyltransferase inhibitor, which restored sensitivity to cisplatin in cell lines 73 . A phase I study of guadecitabine and cisplatin in 14 patients with TGCTs showed an overall response rate of 23% 61 ; excellent responses were also reported in two patients with platinum-refractory disease treated in a phase 1 study of cisplatin, gemcitabine and guadecitabine 62 .…”
Section: Platinum-resistant Disease and Novel Treatmentsmentioning
confidence: 98%